Development of a strain dependent pressure law for superplastic forming of 2024 aluminium alloy: Entwicklung eines dehnungsabhängigen Druckgesetzes zur superplastischen Formgebung der Aluminiumlegierung 2024. Issue 10 (19th October 2017) - Du, R.; Feng, J.; Giraud, E.; Santo, P. D.
Abstract: Superplastic forming is widely used in aeronautic industry to produce complex parts due to the ability of the material to sustain very large deformation. One of the main problems lies in the determination of the pressure law applied during the process to control the strain rate evolution. Many algorithms exist in numerical codes to predict the pressure law, but they generally use a constant value of maximum strain rate as reference to control the pressure law. These simulations give globally good results while lead to long cycle times. In this work, the pressure law is computed in order to control the forming process by a non‐constant strain rate. The value of the optimum strain rate is indeed adapted to the level of strain developed within the part during the forming. This approach is applied on the 2024 aluminium alloy. Uniaxial tensile tests are performed to determine the influence of strain level on the maximum allowable strain rate. Then, the new pressure control algorithm is implemented in the ABAQUS code. Numerical simulations of generic parts are finally performed and the results show a significant reduction of the forming time without decreasing the quality of the parts.